Self-directed learning research: An imperative for transforming the educational landscape - Oosthuizen, Izak (AOSIS, 2016)
This book will benefit specialists in the field of the education sciences. It represents significant progress in knowledge production. Self-directed learning has become increasingly important, not only for education in South Africa but also for education sciences in the international arena. This is a result of the changing education landscape, caused by the demands of the 21st century as well as the rapid change in knowledge production. Learners should be equipped with skills to take responsibility for their own learning. New innovative strategies should be incorporated into teaching and learning in order to meet the changing demands in education. Traditional teacher-centred practices are still the norm in most South African schools and higher-education institutions and do not adequately prepare students for lifelong learning in the 21st century. The content focuses on the theory behind self-directed learning, explores strategies such as cooperative learning, problembased learning, case-based teaching and large-group teaching that enhance self-directed learning and the use of blended learning in a self-directed learning environment. The book demonstrates how self-directed learning can be enhanced in mathematics, computer-science and life-science education and through the use of student tutors for geography. Digital technology could, for example, also be used in innovative ways for education in isiZulu folk poetry. The findings are based on original empirical research and a sound theoretical-conceptual framework. In an environment of rapidly changing knowledge production, this book responds to the challenge of how to equip learners with the necessary skills to take responsibility for their own learning. The book presents innovative teaching and learning strategies for meeting the changing demands in education. Group activities, the responsibilities of learners and the obstacles that hinder their learning are analysed, and the way in which educators can support them is discussed. Educational values such as mutual trust are discussed, and self-directed assessment is explored. This is a timely collective work authored by experts who subscribe to the approach of self-directed learning. Educators should discover new teaching and learning strategies and value the integration of self-directed learning in the classroom.